Immunolocalization of beta catenin in intestinal polyps of Peutz-Jeghers and juvenile polyposis syndromes. Issue 5 (1st May 1999) - Back, W; Loff, S; Jenne, D; Bleyl, U
Abstract : AIM: To examine the membranous and nuclear distribution of beta catenin in the epithelial cells of gut polyps from Peutz-Jeghers syndrome and juvenile polyposis in comparison with other types of polyps and tumours. METHODS: Immunohistochemistry for beta catenin and proliferation markers was performed on conventional paraffin sections. Immunohistological staining was carried out on Peutz-Jeghers syndrome polyps from four different families, on juvenile polyposis polyps from two different families, on solitary juvenile polyps, and on hyperplastic polyps. The immunohistochemistry was evaluated qualitatively in relation to defined areas of the polyps. RESULTS: All polyps from the hamartomatous polyposis syndromes (Peutz-Jeghers syndrome and juvenile polyposis) showed nuclear localization of beta catenin in some epithelial cell nuclei. In Peutz-Jeghers syndrome polyps beta catenin positive nuclei were seen at the base of the deep crypt infoldings. In juvenile polyposis polyps and in some solitary juvenile polyps they were found in irregularly distributed cryptal epithelial cells corresponding to the proliferative compartments. Normal mucosa of the gut and hyperplastic polyps of the colon do not show nuclear staining for beta catenin. CONCLUSIONS: The dysregulation of cellular beta catenin distribution is not only a phenomenon of adenoma formation and adenoma progression in the colon--it is at least focally present in polyps of the hamartomatous type and is related to the proliferation zones of these polyps. The nuclear translocation of beta catenin most probably reflects a disturbed beta catenin metabolism. In view of the different functions of beta catenin during development and cell differentiation, the nuclear translocation of beta catenin is likely to be an important factor in enhanced cell proliferation which escapes local control mechanisms.